Toxicidade do cianeto e interferência na seleção da dieta em codornas - Silva, Roberta Cristina da Rocha e (Universidade Federal Rural do Semi-Árido, 2009)
Cyanide is an ubiquitous substance on environment. Most of the cyanide absorbed by an animal is detoxified by enzymatic combination with sulfur, thus the detoxification process imposes a nutritional cost. In mammals, interactions among nutrients and toxics may influence the composition of the diet and food intake, as a function of positive or negative post-ingestive feedback. The present work aimed to describe the toxic effects of cyanide, and to determine whether cyanide interferes with diet selection in quail (Coturnix coturnix). A toxicological study was performed with 27 female quail that were assigned to three groups that received by gavage 0, 1.0 or 3.0 mg of KCN/kg/day, for 7 consecutive days. The diet selection trial was conducted with 20 female quail. They had access to two separate rations: a conventional quail ration and the same ration supplemented with 1% NaSO4. After 2 days the quail were randomly distributed into two groups, which were dosed with 0 or 3.0 mg of KCN/kg/day, for 5 consecutive days. During the toxicological study, clinical signs of poisoning and death occurred in a quail treated with cyanide. Histological changes were found only in animals dosed with cyanide, and these consisted of mild hepatic periportal vacuolation, an increased number of vacuoles in the colloid of the thyroid glands, and spongiosis in the mesencephalon. No clinical signs were found in any quail throughout the diet selection trial. There were no significant differences in food consumption or ration preference. In conclusion, exposure to cyanide promotes damage to the liver and central nervous system in quail. However, the ingestion of sulfur by quail was not affected by exposure to cyanide.
Cyanide toxicity and interference with diet selection in quail (coturnix coturnix)
Keywords: Cyanide; nutrient-toxin interactions; preference; choice; Cianeto; interação entre nutrientes e toxinas; preferência; escolha; CIENCIAS AGRARIAS::MEDICINA VETERINARIA